2015
DOI: 10.1112/jlms/jdv012
|View full text |Cite
|
Sign up to set email alerts
|

Induced automorphisms on irreducible symplectic manifolds:

Abstract: We introduce the notion of induced automorphisms in order to state a criterion to determine whether a given automorphism on a manifold of K3 [n] -type is, in fact, induced by an automorphism of a K3 surface and the manifold is a moduli space of stable objects on the K3. This criterion is applied to the classification of non-symplectic prime order automorphisms on manifolds of K3 [2] -type and we prove that almost all cases are covered. Variations of this notion and the above criterion are introduced and discus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 26 publications
2
53
1
Order By: Relevance
“…Using the exponential sequence we can find a B-field lift of α, i.e. a class B ∈ H 2 (Σ, Q) such that kB is integral and the map α : Tr(Σ) → Z/kZ is just the intersection product with kB (see [28, §3] In the case α = 0, which was already studied in [4] and [40], it is possible to provide some additional details on the action of induced automorphisms. Let v ∈ H * (Σ, Z) be a primitive, positive Mukai vector; then M v (Σ, 0) is isomorphic to the moduli space M τ (v) of τ -stable objects of Mukai vector v, for τ ∈ Stab(Σ) a v-generic Bridgeland stability condition on the derived category D b (Σ) (see [15] for details).…”
Section: Induced Automorphismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the exponential sequence we can find a B-field lift of α, i.e. a class B ∈ H 2 (Σ, Q) such that kB is integral and the map α : Tr(Σ) → Z/kZ is just the intersection product with kB (see [28, §3] In the case α = 0, which was already studied in [4] and [40], it is possible to provide some additional details on the action of induced automorphisms. Let v ∈ H * (Σ, Z) be a primitive, positive Mukai vector; then M v (Σ, 0) is isomorphic to the moduli space M τ (v) of τ -stable objects of Mukai vector v, for τ ∈ Stab(Σ) a v-generic Bridgeland stability condition on the derived category D b (Σ) (see [15] for details).…”
Section: Induced Automorphismsmentioning
confidence: 99%
“…For n ≥ 3, it is necessary to expand our pool of tools. Induced automorphisms on moduli spaces of (possibly twisted) sheaves on K3 surfaces, studied in [40] and [20], directly generalize natural automorphisms and allow to realize many new pairs (T, S): we show, in Section 5, how to apply these constructions when n = 3, 4. Admissible pairs (T, S) where T has rank one require special attention.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they found that there is a unique 19‐dimensional irreducible family that admits the invariant lattice from each of the cases 1, 2, 4, respectively, and two families in the case 3. The families in the cases 1, 3, 4 admit polarizations of Beauville degree q=2, it is not hard to see [, Remark 5.7] that they can be described as families of resolutions of special singular double EPW sextics.…”
Section: First Construction — Singular Epw Cubesmentioning
confidence: 99%
“…The description as double covers of Lagrangian degeneracy loci can also be applied to study degenerations of the family scriptU and permit to complete the classification of geometric realizations of automorphisms of IHS of type K3[2] given in . Note that as a direct consequence from [, § 5.1] we obtain the following.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation